2015
DOI: 10.1086/679703
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wall Shear Stress in the Assessment of Right Ventricle Hydraulic Workload

Abstract: Pulmonary hypertension (PH) is a devastating disease affecting approximately 15-50 people per million, with a higher incidence in women. PH mortality is mostly attributed to right ventricle (RV) failure, which results from RV hypotrophy due to an overburdened hydraulic workload. The objective of this study is to correlate wall shear stress (WSS) with hemodynamic metrics that are generally accepted as clinical indicators of RV workload and are well correlated with disease outcome. Retrospective right heart cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Tang et al [4] showed that computationally measured WSS is decreased in adult PH, when compared against a healthy control population, which we recently correlated with impedance [22]. Truong et al [3] used phase-contrast MRI to confirm the same finding in pediatric patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Tang et al [4] showed that computationally measured WSS is decreased in adult PH, when compared against a healthy control population, which we recently correlated with impedance [22]. Truong et al [3] used phase-contrast MRI to confirm the same finding in pediatric patients.…”
Section: Discussionsupporting
confidence: 53%
“…Further computational work, comparing pulmonary hemodynamics in the PH patient population with a healthy dataset, revealed a decreased in WSS PH [4], which we recently correlated with an increase in impedance using a similar computational framework [22]. However, the considerations critical to computational modeling of the pulmonary vasculature or the mechanisms driving this WSS decrease remain unaddressed.…”
Section: Introductionmentioning
confidence: 86%
“…Based on computational modeling results, an increase in PVR has been shown to be proportional to a decrease in WSS, which is also a function of the velocity gradient (4). This is consistent with the fact that vorticity decreases concurrently with an increase in PVR in all generations of the vascular tree (31).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in resistance inevitably impacts blood flow patterns in the proximal vessels (4) that are also partially governed by changes in vascular distensibility, morphology, and right ventricular (RV) ejection behavior.…”
Section: Introductionmentioning
confidence: 99%
“…() Our previous studies have also shown that CFD results in the pulmonary circulation are consistent with observational studies in pulmonary hypertension and highly correlated with functional clinical markers of pulmonary vascular disease. ()…”
Section: Final Remarksmentioning
confidence: 99%